Experimental gel containing bioactive glass-ceramic to minimize the pulp damage caused by dental bleaching in rats - Carminatti, Marina [UNESP]; Benetti, Francine [UNESP]; Siqueira, Renato Luiz; Zanotto, Edgar Dutra; Briso, André Luiz Fraga [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (FapUNIFESP (SciELO), 2020)
Objectives: This study evaluated if the use of a bioactive glass-ceramicbased gel, named Biosilicate (BS), before, after or mixed with bleaching gel, could influence the inflammation of the dental pulp tissue of rats’ molars undergoing dental bleaching with hydrogen peroxide (H2O2). Methodology: The upper molars of Wistar rats (Rattus norvegicus, albinus) were divided into Ble: bleached (35% H2O2, 30-min); Ble-BS: bleached and followed by BS-based gel application (20 min); BS-Ble: BS-based gel application and then bleaching; BS/7d-Ble: BS-based gel applications for 7 days and then bleaching; Ble+BS: blend of H2O2 with BS-based gel (1:1, 30-min); and control: placebo gel. After 2 and 30 days (n=10), the rats were euthanized for histological evaluation. The Kruskal-Wallis and Dunn statistical tests were performed (P<0.05). Results: At 2 days, the Ble and Ble-BS groups had significant alterations in the pulp tissue, with an area of necrosis. The groups with the application of BS-based gel before H2O2 had moderate inflammation and partial disorganization in the occlusal third of the coronary pulp and were significantly different from the Ble in the middle and cervical thirds (P<0.05). The most favorable results were observed in the Ble+BS, which was similar to the control in all thirds of the coronary pulp (P>0.05). At 30 days, the pulp tissue was organized and the bleached groups presented tertiary dentin deposition. The Ble group had the highest deposition of tertiary dentin, followed by the Ble-BS, and both were different from control (P<0.05). Conclusion: A single BS-based gel application beforehand or BS-based gel blended with a bleaching gel minimize the pulp damage induced by dental bleaching.
Keywords: Bioactive glass; Dental pulp; Hydrogen peroxide; Tooth bleaching; Tooth remineralization